THE PERSPECTIVES OF ACEHNESE ULAMA AND EDUCATION EXPERTS IN SHAPING IAIN LHOKSEUMAWE AS CAMPUS OF CIVILIZATION - Daud, Al Husaini M; Usman, Munadi; Nuraini, Nuraini (MIQOT: Jurnal Ilmu-ilmu Keislaman, 2020)
Abstract: This article discusses about a search of the resources of Islamic Civilization as perceived by Acehnese Islamic scholars and education practitioners in the context of shaping a campus of civilization. This study is a qualitative research applying phenomenology approach. Most data were acquired from informants who are directly related to the theme in question. From the results of the field data, it was found that the main sources of a solid civilization, according to scholars and figures of Aceh education, were the Qur’an and the Sunnah of the Prophet, the plurality of Islamic societies, and the results of external Islamic civilization. The three main sources of Islamic civilization became the initial basis for the development of a civilized campus in its true meaning.Keywords: Islamic civilization sources, ulama, campus of civilization